Still waiting for Godot?: Improving Household Consumption and Expenditures Surveys (HCES) to enable more evidence-based nutrition policies - Fiedler, John L.; Carletto, Calogero; Dupriez, Olivier (SAGE Publications, 2012)
The constrained evidence base of food and nutrition policy-making compromises nutrition programs. Nutrition policy-making must do better than relying exclusively on Food and Agriculture Organization Food Balance Sheets. The strategy of relying on observed-weighed food record or 24-hour recall surveys has not proven practical either; they remain few in number, generally not nationally representative, and of dubious external validity. Although Household Consumption and Expenditures Surveys (HCES) have shortcomings, they are increasingly being used to address this information gap.To promote dialog within the nutrition community, and between it and the greater community of HCES stakeholders, in order to identify their shared agenda and develop a strategy to improve HCES for analyzing food and nutrition issues.The diverse origins and objectives of HCES are described, the evolution of their use in addressing food and nutrition issues is traced, and their shortcomings are identified.The causes, relative importance, some potential solutions, and the strategic implications of three distinct categories of shortcomings are discussed. Elements of a possible approach and process for strengthening the surveys are outlined, including identifying best practices, developing guidelines and more rigorously analyzing the tradeoffs involved in common, key survey design and implementation decisions.To date, the nutrition community's role in most HCES has been as a passive user of secondary data. The nutrition community must become more involved in the design, implementation, and analysis of HCES by identifying criteria for prioritizing countries, establishing assessment criteria, applying the criteria in retrospective assessments, identifying key shortcomings, and recommending alternatives to ameliorate the short-comings. Several trends suggest that this is a propitious time for improving the relevance and reliability of HCES.